Tunis hosts the consultation workshop on strengthening Tunisia’s innovation ecosystem for climate-resilient agriculture - Mounir, Aya; Zaccari, Claudia (2025)
On 20 May 2025, over 100 industry experts gathered at the Hotel Golden Carthage Gammarth, in Tunis, for the Consultation Workshop: Strengthening Tunisia's Innovation Ecosystem for Climate-resilient Agriculture. This event showcased the pivotal role of research, technology, and entrepreneurship in driving sustainable and resilient agriculture in Tunisia. Read the Wrap Up Blog Post.